An Investigation into English Medium Education in Sri Lanka with Special reference to Content Based Instruction at Junior Secondary Level - Kularathne, S.A. (My University, 2004)
The aim of this study is to examine recently re introduced English medium education at junior secondary level. The teaching learning process in English medium education and teacher education programmes implemented to this effect are investigated into in this study. The title of this research; an investigation into English Medium Education at Junior Secondary Level with special reference to Content Based Instruction (CBI) was specially selected as the statement of problem, due to two reasons . 1. To study the classroom practice in English medium education. 2. To suggest recommendations to improve the teaching learning process in English medium education at junior secondary level. The abrupt introduction of English medium education, lack of competent teachers in schools to teach the prescribed subjects in English medium, the absence of a proper on going and post supervision scheme for evaluation too were other reasons that compelled the researcher to select the topic. The study was carried out in relation to four objectives. Content Based Instruction (CBI) is one of the approaches used widely in teaching English as a second language in different parts of the world. Hence selected methodologies and approaches in teaching English as a Second language in different context were surveyed in the literature review. One of the objectives of the literature review was to explore possibilities of such second language teaching methods and approaches in teaching Content Based Instructions at Junior Secondary level. The sample of this study was ten schools where English Medium Education was implemented. Twenty questionnaires were administered to twenty teachers and out of them fifteen questions were selected for analysis.